Chemical and Spectrophotometric Investigations of 3-Mercapto- 5,6-diphenyl-1,2,4-triazine as a New Carboxyl Activating Group - RAJAN, M.P. (Asian Journal of Chemistry, 2010)
The synthesis of 3-mercapto-5,6-diphenyl-1,2,4-triazine and its benzoyl derivatives and the subsequent conversion of respective amides and esters using chemical as well as spectrophotometric tools are described. This paved the way for the introduction of a new and versatile carboxyl activating group which was more effective than conventional carboxyl activating groups that usually apply in the solid phase peptide synthesis.